2003
DOI: 10.1034/j.1600-0706.2003.12571.x
|View full text |Cite
|
Sign up to set email alerts
|

Mixed blends of herbivore‐induced plant volatiles and foraging success of carnivorous arthropods

Abstract: Dicke, M., de Boer, J. G., Hö fte, M. and Rocha-Granados, M. C. 2003. Mixed blends of herbivore-induced plant volatiles and foraging success of carnivorous arthropods. Oikos 101: 38 -48.Food webs are overlaid with infochemical webs that mediate direct and indirect interactions. Behavioural ecologists have extensively documented that carnivorous arthropods exploit herbivore-induced plant volatiles during foraging for herbivorous arthropods. Most studies on the role of infochemicals in multitrophic interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
2
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 55 publications
0
47
2
1
Order By: Relevance
“…A number of cases have been reported where predatory arthropods and parasitoids respond to HIPV from plants with non-prey or non-host herbivores (Agrawal and Colfer 2000;Shimoda and Dicke 2000;Thaler et al 2002;Dicke et al 2003;Van Poecke and Dicke 2003;A. Janssen and M. Van Wijk 2005, unpublished data).…”
Section: Learning To Cope With Variability In Hipv From Singly and Mumentioning
confidence: 99%
“…A number of cases have been reported where predatory arthropods and parasitoids respond to HIPV from plants with non-prey or non-host herbivores (Agrawal and Colfer 2000;Shimoda and Dicke 2000;Thaler et al 2002;Dicke et al 2003;Van Poecke and Dicke 2003;A. Janssen and M. Van Wijk 2005, unpublished data).…”
Section: Learning To Cope With Variability In Hipv From Singly and Mumentioning
confidence: 99%
“…1). Besides the olfactometer, we used a greenhouse set-up that resembled the situation in the field more closely, with intact plants standing in soil (Pallini et al, 1997;Janssen, 1999;Dicke et al, 2003a). This experiment confirmed that the foraging efficiency of predatory mites was not hampered by the presence of P. brassicae-infested brussels sprouts plants (Dicke et al, 2003a).…”
Section: Foraging In An Environment With Non-prey Herbivoresmentioning
confidence: 53%
“…Moreover, P. persimilis was not attracted to the volatiles from P. brassicae-infested brussels sprouts plants (Dicke et al, 2003a). This may indicate that the volatiles emitted by P. brassicae-infested brussels sprouts plants do not play a role in the foraging behaviour of P. persimilis and therefore do not disturb its foraging efficiency when mixed with volatiles from prey-infested bean plants.…”
Section: Foraging In An Environment With Non-prey Herbivoresmentioning
confidence: 68%
See 1 more Smart Citation
“…Successful parasitism requires a series of interactions among parasitoids, their hosts and host plants, including habitat fi nding, host location, host acceptance, host suitability and host regulation (Vinson, 1976(Vinson, , 1984Hatano et al, 2008;Rasekh et al, 2010). Parasitoids may respond to semiochemical cues during antennal contact and ovipositor probing (Muratori et al, 2006;Larocca et al, 2007) and volatile chemical compounds emitted by damaged plants (Turlings et al, 1990, Mattiacci et al, 1994, Dicke et al, 2003. Host selection by parasitoids may be infl uenced by the insect host, the plant on which the insect hosts are feeding and by conditioning of females to the host on which they developed (Chau & Mackauer, 2001).…”
Section: Methodsmentioning
confidence: 99%